Análise do equilíbrio postural de indivíduos diabéticos por meio de baropodometria - Nozabieli, A. J. [UNESP]; Martinelli, A. R. [UNESP]; Mantovani, A. M. [UNESP]; Faria, C. R. [UNESP]; Ferreira, D. M. [UNESP]; Fregonesi, C. E. [UNESP] (Desafio Singular, Lda, 2012)
Objective of this study was to analyze the postural balance of neuropathic diabetic individuals through baropodometry, related to losses in the sensorimotor system. Twenty-eight healthy and 25 diagnosed with diabetic neuropathy were subjected to static evaluation (measurement of displacement of body center of pressure) and dynamic (temporal analysis of the stance phase of gait cycle). The tactile sensitivity of the feet was assessed by Semmes Weinstein monofilaments and isometric muscle strength of ankle dynamometry. Analyses of multivariânvia (MANOVAs) and variance (ANOVAs) indicated lower performance in tactile sensitivity, muscle strength and dynamic balance, but showed no difference for static equilibrium of diabetic neuropathy. With this study by regression analysis, one can infer that the equilibrium differences in gait of neuropathic insensitivity may result from tactile and muscle strength. © FTCD/FIP-MOC.
Postural control analysis of diabetic individuals through baropodometry
Keywords: Diabetes mellitus; Diabetic neuropathy; Muscle strength; Postural control